2011
DOI: 10.1176/appi.ps.62.8.893
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of Self-Stigma Among Adolescents Taking Psychiatric Medication

Abstract: Objective:The extant literature describes stigma in two forms, public stigma and self-stigma. Public stigma pertains to negative social behaviors, reactions, attitudes, and beliefs directed toward people with mental illness and among persons with mental illness. Self-stigma concerns the internalized effects of public stigma. Although both types of stigma have negative impacts on people with mental illness, they produce different effects. In particular, self-stigma can negatively affect self-esteem, social rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 9 publications
1
58
0
Order By: Relevance
“…The inverse relationship between self esteem and self stigma was reported in previous studies [7-9,28] and when we talk of self stigma, it is more or less directly or indirectly related with self esteem. In line with the above mentioned literature, a significant inverse relationship was found between self esteem on the one hand, and stereotype endorsement, stigma resistance and the overall self stigma scores on the other hand.…”
Section: Discussionsupporting
confidence: 64%
“…The inverse relationship between self esteem and self stigma was reported in previous studies [7-9,28] and when we talk of self stigma, it is more or less directly or indirectly related with self esteem. In line with the above mentioned literature, a significant inverse relationship was found between self esteem on the one hand, and stereotype endorsement, stigma resistance and the overall self stigma scores on the other hand.…”
Section: Discussionsupporting
confidence: 64%
“…The experience of the lone African American student raises important questions regarding the influence of familial perceptions on psychiatric treatment and community integration. Recent research [10] indicates that African American adolescents have a more intense experience of self-stigma in comparison with White adolescents. This was attributed to African American families expressing more negative views about mental illness stereotypes and characteristics to their children who have a psychiatric disability.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research should be conducted at a variety of university and college settings including public and private institutions, community colleges, institutions with military or faith-based ties, and those in different geographic locations. Students of diverse races and cultures would be crucial groups to compare, especially since research [10,14] indicates minority groups' reluctance to utilize psychiatric medications, and negative perceptions toward help-seeking for mental illness. In addition, minority students may experience multiple stigmas, which could increase the level of stigma they experience with regards to mental health concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Floersch et al (2009) conducted interviews with adolescents about their subjective experiences with psychotropic medication therapy and found that although youth believed in the need for and effectiveness of psychotropic medication, they had many questions about how these medications work and substantial concerns about side effects. Floersch et al (2009) suggested that these results occurred because of a large gap in the experience and knowledge of youth regarding the effects and side effects of medication.Additionally, Kranke, Floersch, Kranke, and Munson (2011) conducted interviews with adolescents about their subjective experiences with psychotropic medication therapy, and found an association between taking medications and self-stigma. Specifically, many adolescents had experienced stigma and shame related to their condition and therefore preferred not to disclose their use of psychotropic medication.…”
mentioning
confidence: 99%